Triangle Love Reflected At Haruki Murakami's Sputnik Sweetheart (1999) Novel: An Individual Psychological Approach - Sari, Linda Yunita; , Dr. Phil. Dewi Candraningrum, M.Ed; , Titis Setyabudi, S.S., M. Hum (2015)
This major problem of this study is to describe how is the triangle love reflected at Haruki Murakami's novel. The object of the study is Sputnik Sweetheart novel written by Haruki Murakami. The research consists of two objectives as follows; to analyze the novel based on its structural elements and to analyze the novel based on an individual psychological approach. In analyzing Sputnik Sweetheart novel, the writer uses qualitative method and an individual psychological approach. The object of the study is Haruki Murakami Sputnik Sweetheart novel which was published by Harvill Press on 1999, in the Great Britain and consists of more than 220 pages. The data sources consist of primary data and secondary data sources. The primary data source is the Sputnik Sweetheart novel itself and the secondary data sources are books or any information related the subject that supports the psychological approach. The technique of data collection is Reading the novel repeatedly, Identifying the problem and find the data, Collecting some supporting data from other references related to the topic, Selecting particular parts considered important and relevant for analysis and Drawing conclusion and formulate its pedagogical suggestion. The technique of data analysis is descriptive analysis. Based on the analysis, the writer draws some conclusions as follow: First, based on the structural analysis, it can be concluded that the author of the novel delivered message that the love cannot limited with gender and time. Second, based on an individual psychological approach, it can be concluded that Sumire illustrated a psychological phenomenal reflects the life of an individual is very much complicated with the triangle love and loneliness.